2018
DOI: 10.6001/biologija.v63i4.3608
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting Zantedeschia Spreng. dedifferentiation in vitro

Abstract: Zantedeschia Spreng. is an economically important ornamental plant species. Improvement of aesthetic parameters and creation of novel variations of decorative plants are important economic goals for the commercial ornamental industry. The effect of the combination of growth regulators and the explant type on dedifferentiation induction in Zantedeschia aethiopica and Zantedeschia elliottianna was investigated. Research was carried out at the Institute of Biology and Plant Biotechnology of Aleksandras Stulginski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…The application of exogenous cryoprotectants containing proline significantly elevates the endogenous proline levels and enhances cold tolerance. Studies have shown that prolinemediated cryoprotectant treatments in rapeseed shoots increase cold tolerance and reduce electrolyte leakage, which is an indicator of membrane injury (Jonytiene et al, 2012). Additionally, prolinetreated Brassica juncea has been shown to protect isolated thylakoid membranes from photoinhibition (Bhandari and Nayyar, 2014) and improve the maintenance of chloroplast ultrastructure and membrane integrity in tobacco plants (Van Rensburg et al, 1993).…”
Section: Stabilizing Cellular Structuresmentioning
confidence: 99%
“…The application of exogenous cryoprotectants containing proline significantly elevates the endogenous proline levels and enhances cold tolerance. Studies have shown that prolinemediated cryoprotectant treatments in rapeseed shoots increase cold tolerance and reduce electrolyte leakage, which is an indicator of membrane injury (Jonytiene et al, 2012). Additionally, prolinetreated Brassica juncea has been shown to protect isolated thylakoid membranes from photoinhibition (Bhandari and Nayyar, 2014) and improve the maintenance of chloroplast ultrastructure and membrane integrity in tobacco plants (Van Rensburg et al, 1993).…”
Section: Stabilizing Cellular Structuresmentioning
confidence: 99%
“…Calla lilies in the Zantedeschia section have white flowers while those in the Aestivae section have a variety of colours. Consequently, there are several varieties of calla lily used as cut flowers and pot plants depending on the flower shape and colours (Jonytienė et al, 2017) and the vase life (Lazzereschi et al, 2011). Commercially, calla lily is one of the major cut flowers traded on the international market.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Z. aethiopica and Z. hybrida (interspecies hybrids mainly generated from Z. elliotiana , Z. pentlandii , Z. albinoscapulata , and Z. rehmannii , etc. ) have been utilized for induction, and variation in induction rates of Z. aethiopica was 16.3% while Z. hybrida was 24.4% ( Jonytienė et al, 2017 ). In conclusion, the combination and concentration of PGRs have been thoroughly examined to evaluate their effects on several plant tissue culture regeneration processes, such as callus formation and root induction.…”
Section: Introductionmentioning
confidence: 99%